Pengaruh Pengurangan Kadar Air dan Penggunaan Bahan Pengikat Kadar Air dalam Pembuatan Cake Bengkuang - Wilsa Hermianti; Yulia Helmi Diza; Firdausni Firdausni; Tri Wahyuningsih (Institution for Industrial Research and Standardization of Industry - Padang, 2016)
Yam contains a high water content ranging from 86-90% therefore when be processed to be a product such as cake will also result a high water content and cause the product is not durable. By the nature characteristics of the yam was then made utilization efforts became yam cake in order to develop yam processing, increase value added, and diversify food processing based on raw materials of local potential in Padang City. Yam can be used by processing them into a semi wet food such as cake with a dominant amount of yam up to 50% of the cake batter, but only had a shelf life for 3 days. To increase the shelf-life study was carried out water content reduction of raw materials and using of a binder in the making of yam cake. The treatment of water content reduction of yam was done using juicer and pressing. A comparison as a control was performed without reduction of water content. The use of water content binder was conducted with the addition of coconut, cornstarch, and rice flour. Yam cake formulas using binder of water content with cornstarch and reduction the water content of raw material by pressing showed optimal results with a preferred value of organoleptic panelist, the water content 28.50%, carbohydrate 56.31%, protein 6.13%, fat 10.23%, energy 341.86 kcal/100g, dietary fiber 5.98%, calcium 27.77 mg/100g, and 5.92% inulin, storability for 5 days at room temperature and 4 weeks at refrigerator temperature.ABSTRAKBengkuang mengandung kadar air yang tinggi berkisar 86-90% sehingga jika diolah untuk menjadi produk berupa cake akan memberikan kadar air yang juga tinggi dan menyebabkan produk menjadi tidak tahan lama. Dengan sifat alami bengkuang tersebut maka dilakukan upaya pemanfaatannya menjadi cake bengkuang dalam rangka pengembangan olahan dari bengkuang, peningkatan nilai tambah, dan diversifikasi olahan pangan berbasis bahan baku lokal yang cukup potensi di kota Padang. Bengkuang dapat dimanfaatkan dengan mengolahnya menjadi pangan semi basah berupa cake bengkuang dengan jumlah bengkuang yang dominan yakni sampai 50% dari adonan cake namun hanya mempunyai ketahanan simpan selama 3 hari. Guna meningkatkan masa simpannya dilakukan penelitian pengurangan kadar air bahan baku bengkuang dan penggunaan bahan pengikat dalam pembuatan cake bengkuang. Perlakuan pengurangan kadar air bengkuang dilakukan dengan menggunakan juicer dan dipress. Sebagai pembanding (kontrol) dilakukan tanpa pengurangan kadar air. Penggunaan bahan pengikat kadar air bengkuang adalah dengan penambahan kelapa, tepung maizena, dan tepung beras. Cake bengkuang menggunakan formula bahan pengikat kandungan air bengkuang dengan tepung maizena serta pengurangan kadar air bahan baku bengkuang dengan dipress memberikan hasil yang optimal dengan nilai organoleptik yang disukai panelis, kadar air 28,50%, karbohidrat 56,31%, protein 6,13%, lemak 10,23%, energi 341,86 kkal/100g, serat pangan 5,98%, kalsium 27,77mg/100g, dan inulin 5,92%, daya simpan selama 5 hari pada suhu kamar dan 4 minggu pada suhu kulkas.